Chronic helminth infection does not impair immune response to malaria transmission blocking vaccine Pfs230D1-EPA/Alhydrogel® in mice. Issue 8 (14th February 2019) - Coelho, Camila H.; Gazzinelli-Guimaraes, Pedro Henrique; Howard, Jennifer; Barnafo, Emma; Alani, Nada A.H.; Muratova, Olga; McCormack, Ashley; Kelnhofer, Emily; Urban, Joseph F.; Narum, David L.; Anderson, Charles; Langhorne, Jean; et al.
Highlights: Pfs230 is a candidate malaria transmission blocking vaccine against P. falciparum. Pfs230 vaccine is being tested in areas where malaria and helminth infections are co-endemic. Chronic helminth infection induces a marked increase in systemic Th2 and regulatory cytokine levels in mice. Chronic H. polygyrus bakeri infection does not alter Pfs230 vaccine specific-antibody levels. Functional activity of Pfs230 vaccine was not impaired by chronic helminth infection in mice. Abstract: Introduction: Malaria transmission blocking vaccines (TBV) are innovative approaches that aim to induce immunity in humans against Plasmodium during mosquito stage, neutralizing the capacity of the infected vectors to transmit malaria. Pfs230D1-EPA/Alhydrogel®, a promising protein-protein conjugate malaria TBV, is currently being tested in human clinical trials in areas where P. falciparum malaria is coendemic with helminth parasites. Helminths are complex metazoans that share the master capacity to downregulate the host immune response towards themselves and also to bystander antigens, including vaccines. However, it is not known whether the activity of a protein-based malaria TBV may be affected by a chronic helminth infection. Methods: Using an experimental murine model for a chronic helminth infection ( Heligmosomoides polygyrus bakeri - Hpb), we evaluated whether prior infection alters the activity of Pfs230D1-EPA/Alhydrogel® TBV in mice. Results: After establishment of a chronic infection, characterized by a marked increase of parasite antigen-specific IgG1, IgA and IgE antibody responses, concomitant with an increase of systemic IL-10, IL-5 and IL-6 levels, the Hpb-infected mice were immunized with Pfs230D1-EPA/Alhydrogel® and the vaccine-specific immune response was compared with that in non-infected immunized mice. TBV immunizations induced an elevated vaccine specific-antibody response, however Pfs230D1 specific-IgG levels were similar between infected and uninfected mice at days 15, 25 and 35 post-vaccination. Absolute numbers of Pfs230D1-activated B cells generated in response to the vaccine were also similar among the vaccinated groups. Finally, vaccine activity assessed by reduction of oocyst number in P. falciparum infected mosquitoes was similar between Hpb-infected and immunized mice with non-infected immunized mice. Conclusion: Pfs230D1-EPA/Alhydrogel® efficacy is not impaired by a chronic helminth infection in mice.